Asymmetric dual catalysis via fragmentation of a single rhodium precursor complex. Issue 49 (27th May 2016) - Song, Liangliang; Gong, Lei; Meggers, Eric
Abstract : A strategy for dual transition metal catalysis and organocatalysis is reported via disintegration of a single rhodium complex. Conveniently, the chiral-at-metal rhodium precatalyst can be synthesized in just two steps starting from rhodium trichloride without the need for any chromatography. Abstract : A strategy for dual transition metal catalysis and organocatalysis is reported via the in situ disintegration of a single rhodium complex. The hereby generated chiral Lewis acid andl -β-phenylalanine synergistically catalyze the Michael addition of α, α-disubstituted aldehydes to α, β-unsaturated 2-acyl imidazoles under the formation of vicinal quaternary/tertiary stereocenters. Conveniently, the chiral-at-metal rhodium catalyst can be synthesized in just two steps starting from rhodium trichloride without the need for any chromatography.